The Effectiveness of the Traditional Congklak Game in Developing Fine Motor Skills in Early Childhood at the Kasih Bunda Kindergarten, South Aceh - Erlina, Erlina; Mastura, Emi; Herrera, Lilian A.; Norli, Muhammad Asyraf (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The primary objective of this research is to investigate the influence of the traditional game, Congklak, on the development of fine motor skills in early childhood at Kasih Bunda Kindergarten. Methodology: This study employed an experimental research design with a pre-experimental approach. The participants consisted of students from the B2 group at Kasih Bunda Kindergarten, South Aceh, totaling 27 students in the experimental class. Data analysis was conducted using descriptive quantitative methods, comparing the averages of pre-test and post-test data collected through observations. Hypothesis testing was performed using the t-test based on the results of the activity scale. Main Findings: The main finding of this research is the comparison of average values before and after the treatment. With tcount > ttable, specifically 27.30 > 2.056, the null hypothesis (Ho) is rejected, indicating a significant difference between the scores obtained from the initial and final tests at a 95% confidence level. Consequently, it can be concluded that the Congklak game significantly contributes to the development of fine motor skills in young children at Kasih Bunda Kindergarten. Novelty/Originality of this study: The novelty of this research lies in the discovery of the potential of traditional games, such as Congklak, not merely as recreational activities but as effective tools for enhancing young children's fine motor skills, particularly in understanding number concepts and counting activities, thereby making classroom learning more engaging and enjoyable.